FILANTROPI BERBASIS FAITH BASED ORGANIZATION DI INDONESIA (Studi Kasus Program PKPU) - Maryolo, Amril (LP2M IAIN Palopo, 2017)
Philanthropy is an act of generosity that has a sense of sympathy for human beings. Generosity is an integral part of the character of Indonesian society, derived from religious wisdom, culture, and a strong sense of community. The existence of Faith Based Organization (religious-based organization) helps the government in overcoming the social inequalities that occur in middle and lower society. One of the humanitarian organizations based on Islam in Indonesia is the Post of Justice Peduli Ummat (PKPU) which provides assistance, various forms of social activities in various fields. The presence of these humanitarian agencies in Indonesia marks the